Use of cognitive aids and other assistive technology by individuals with multiple sclerosis - JOHNSON, KURT L. (2009)
PURPOSE: To investigate the use of assistive technology (AT), unmet needs for AT, and examine correlates of use of memory aids and cognitive strategies among individuals with multiple sclerosis (MS). METHOD: A cross-sectional study of 1,063 community dwelling adults with MS in Washington State. A self-report survey assessed use of AT as well as depression, fatigue, mobility, and other demographic and disease related variables. RESULTS: Some 70% of respondents reported using memory strategies and 50.7% reported using electronic memory aids. The strongest correlate of use of electronic memory aids was endorsement of difficulties thinking (OR: 2.09, p < 0.001) though younger age, higher education, and report of higher fatigue were also significant. Fatigue (OR: 1.27, p < 0.001) and depression (OR: 0.89, p < 0.001) were highly associated with use of memory strategies. Subjects who were older, unemployed, more depressed, and have more mobility disability were less likely to use memory strategies. CONCULSIONS: Use of AT for memory is widespread and further research should be conducted on efficacy of AT. Many individuals who might be presumed to need AT for memory most (older, less educated, more disability) are least likely to report use. Healthcare providers are urged to ask about memory AT and make appropriate referrals.